Success factors for e-learning in a developing country: A case study of Serbia - Miroslava Raspopovic; Aleksandar Jankulovic; Jovana Runic; Vanja Lucic (International Review of Research in Open and Distributed Learning, 2014)
In this paper, DeLone and McLean’s updated information system model was used to evaluate the success of an e-Learning system and its courses in a transitional country like Serbia. In order to adapt this model to an e-Learning system, suitable success metrics were chosen for each of the evaluation stages. Furthermore, the success metrics for e-Learning evaluation are expanded by providing several systems for quantifying the given success metrics. The results presented in this paper are based on courses that were taught both online and traditionally in three different subject areas: graphic design, information technology, and management. Of particular interest were success metrics which can be determined using quantifiable data from the e-Learning system itself, in order to evaluate and find the relationship between students’ academic achievement, usage of learning materials, and students’ satisfaction. The results from different courses were used to illustrate the implementation and evaluation of these success metrics for both online and traditional students.